Pemanfaatan Canva Untuk Kebutuhan Desain Grafis dan Video Promosi Edotel TeBe Syariah - Andreas Nugroho Sihananto; Kartini Kartini; Rizky Parlika (Prosiding, 2022)
Marketing activities are at the core of every business, even in hospitality business. The hotels today is being challenged in marketing, especially digital marketing, and one of them is Edotel TeBe Syariah which is owned by SMK Tunas Bangsa on Malang City. The challenge faced by Edotel is the lack of human resources who master visual content creation and video creation for digital marketing purposes. Although it has confirmed business cooperation with OYO as SPOT ON 90349 for its marketing channel, the management also wants to strengthen its digital marketing side through social media. Because of the Covid-19 pandemic, the hotel occupancy rate is uncertain, sometimes only a few rooms are filled. The management also wants to increase the capacity of their human resources. our community service team and management plan marketing teaching strategies using Canva-based visual and video content. After using the Canva application for a while, all permanent employees of Edotel TeBe Syariah are now able to use Canva to create visual and video content for marketing needs. We hope that digital marketing activities through social media such as Facebook and Instagram owned by Edotel TeBe Syariah can be further improved